PENINGKATAN KOMPETENSI GURU MELALUI PEMBINAAN GURU DENGAN PENDEKATAN DIREKTIF - herawati, ninik ria; Maunah, Binti (JURNAL KOULUTUS, 2022)
The One of the way to improve the quality of education is to have qualified educators. For this reason, it is necessary for a principal as a supervisor to provide assistance in teacher development so that teacher competence increases. In teacher development itself, there are three approaches that can be used by a supervisor, namely a directive approach, a non-directive approach and a collaborative approach. For a supervisor, the selection of the appropriate approach to be given to teachers in schools has an important role. This is because choosing the appropriate approach will accelerate the improvement of teacher competence and a supervisor will be easier, more effective and efficient in improving the competence of teachers in their schools. Of course, each approach used has its own weakness and strengths that must be considered by a supervisor. In writing this scientific paper, it will focus on the discussion of teacher development with a directive approach. For a more in-depth discussion, this directive approach will be discussed in two areas, namely the understanding of the directive approach and teacher development with the directive approach. Hopefully, through this scientific paper, the readers can find out more about how to improve teacher competence through teacher development with a directive approach. Keywords: teacher development, directive approach